Turkey's Rurality: A Comparative Analysis At the EU Level - Peter Nijkamp; Tuzin Baycan Levent; Aliye Ahu Gulumser (European Regional Science Association (ERSA), 2006)
The future of Europe's rural peripheries as well as the future of rural societies is one of the most important development and planning issues of the EU. Several typologies of rural areas and different rural development indicators have been developed by researchers and international organizations such as OECD and EU to better understand the dynamics of rural areas and to develop relevant policies for these areas. The typologies of rural areas are based on sub-national territories and administrative or statistical units (i.e. local, regional, NUTS3, NUTS5), whereas rural development indicators include a wide range of indicators from population and migration to economic structure and performance and from social well-being and equity to environment and sustainability. Against this background, the aim of this paper is to compare and evaluate Turkey's rurality with the EU-25 countries on the basis of rural development indicators. The data and information used for comparison and evaluation are based on EUROSTAT data. A multicriteria analysis technique, factor analysis is deployed to define Turkey's rurality in the European context. To map out the characteristics and dynamics of Turkey's rurality may also help to develop relevant policies for rural development of the country.
Keywords: 330